1889-90 Va. Acts 118, ch. 152, § 1 - (:unkn) unknown (General Publisher, 1890)
Banned the sale, barter, transfer, giving, or furnishing, or cause to be sold to any minor under sixteen pistols, dirks, Bowie knives. Violators fined not less than ten nor more than one hundred dollars.
--
Keywords: TRANSFER - MINORS